2019
DOI: 10.3390/ijms20133288
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Lipin in the Wing Development of Drosophila melanogaster

Abstract: Lipin is evolutionarily conserved from yeast to mammals. Although its roles in lipid metabolism in adipocyte tissue, skeletal muscle, and the liver, and as a transcriptional co-activator are known, its functions during development are still under investigation. In this study, we analyzed the role of Drosophila lipin (dLipin) in development. Specifically, we showed that the tissue-selective knockdown of dLipin in the wing pouch led to an atrophied wing. Elevated DNA damage was observed in the wing imaginal disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…A previous study showed that rux mutation caused defects in the cell cycle regulation that led to the premature entry into S phase (represented by substantial increases in 5-bromo-2'-deoxyuridine staining), resulting in a similar but more severe rough eye phenotype to that observed in the present study and in the absence of changes in mitosis [32]. Moreover, our recent study of the regulation of the developing wing suggested that the knockdown of dLipin by an sd-GAL4 driver induces the accumulation of cells in S-phase while also decreasing the number of mitotic cells [33]. These studies suggest that increases in S-and M-phase cells can be regulated differently due to cell cycle defects; however, the underlying mechanism needs to be investigated further.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A previous study showed that rux mutation caused defects in the cell cycle regulation that led to the premature entry into S phase (represented by substantial increases in 5-bromo-2'-deoxyuridine staining), resulting in a similar but more severe rough eye phenotype to that observed in the present study and in the absence of changes in mitosis [32]. Moreover, our recent study of the regulation of the developing wing suggested that the knockdown of dLipin by an sd-GAL4 driver induces the accumulation of cells in S-phase while also decreasing the number of mitotic cells [33]. These studies suggest that increases in S-and M-phase cells can be regulated differently due to cell cycle defects; however, the underlying mechanism needs to be investigated further.…”
Section: Discussionsupporting
confidence: 85%
“…Cells in the S-phase were detected using Click-iT EdU (5-ethynyl-2 -deoxyuridine) labeling Alexa Fluor 594 Imaging Kit (Invitrogen, Carlsbad, CA, USA) [33]. Third instar larvae were dissected in phosphate buffer saline (PBS), and the eye discs were fixed in 4% paraformaldehyde for 20 min at 25 • C. After washing with PBS containing 0.3% Triton X-100 (PBST), the samples were blocked with 0.1% PBST and 10% normal goat serum for 30 min at 25 • C, and incubated with diluted primary antibodies in 0.1% PBST and 10% normal goat serum for 16 h at 4 • C [52,53].…”
Section: Immunostainingmentioning
confidence: 99%
“…To reveal that salivary gland cells induce DNA damage by the depletion of LSD-2, we examined the expression of histone variant H2Av phosphorylated at Ser137 (γH2Av), a marker for an early signal of DNA damage induced by replication stress 33 , 34 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The delay in cell entry into the S-phase in KD flies might be associated with DNA damage induced by replication stress 34 . Our results demonstrated that the salivary gland showed an extremely high level of γH2Av protein, a marker of DNA damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation